Sex-dependent effects of Setd1a haploinsufficiency on development and adult behaviour. - Matthew L Bosworth; Anthony R Isles; Lawrence S Wilkinson; Trevor Humby (PLoS ONE)
Loss of function (LoF) mutations affecting the histone methyl transferase SETD1A are implicated in the aetiology of a range of neurodevelopmental disorders including schizophrenia. We examined indices of development and adult behaviour in a mouse model of Setd1a haploinsufficiency, revealing a complex pattern of sex-related differences spanning the pre- and post-natal period. Specifically, male Setd1a+/- mice had smaller placentae at E11.5 and females at E18.5 without any apparent changes in foetal size. In contrast, young male Setd1a+/- mice had lower body weight and showed enhanced growth, leading to equivalent weights by adulthood. Embryonic whole brain RNA-seq analysis revealed expression changes that were significantly enriched for mitochondria-related genes in Setd1a+/ samples. In adulthood, we found enhanced acoustic startle responding in male Setd1a+/- mice which was insentitive to the effects of risperidone, but not haloperidol, both commonly used antipsychotic drugs. We also observed reduced pre-pulse inhibition of acoustic startle, a schizophrenia-relevant phenotype, in both male and female Setd1a+/- mice which could not be rescued by either drug. In the open field and elevated plus maze tests of anxiety, Setd1a haplosufficiency led to more anxiogenic behaviour in both sexes, whereas there were no differences in general motoric ability and memory. Thus, we find evidence for changes in a number of phenotypes which strengthen the support for the use of Setd1a haploinsufficient mice as a model for the biological basis of schizophrenia. Furthermore, our data point towards possible underpinning neural and developmental mechanisms that may be subtly different between the sexes.